DEVELOPMENT OF DESCRIPTIVE TEXT ANIMATION VIDEOS ABOUT LOCAL WISDOM BASED ON QR CODE - Umi Maftuhah; Indri Astuti; Dede Suratman (Jurnal Scientia, 2022)
Abstract This study aims to develop animation video design in learning materials descriptive text about the local wisdom of West Kalimantan which can be accessed by scanning a QR code. The research method used is Research and Development (R&D) with the ADDIE model consisting of stages of analysis, design, development, implementation, and evaluation. The instrument used in the analysis stage was a closed questionnaire with the result that 55.6% of students said the teacher used videos uploaded from the internet. 70.9% of students said the teacher never presented the topic of local culture in learning. In the leger document study, the descriptive text value of 34 students was found to be 58, 7% of students scored below the KKM 80 score. Based on the results of the analysis stage, the researcher made an animated video design using the powtoon application which used descriptive text reading activities. Key Words: Descriptive Text, Local Wisdom, Video Animation